China’s digital shadows: unveiling the economic toll of cybercrime - Yugang He (Humanities & Social Sciences Communications)
Abstract This study investigates the relationship between cybercrime and economic growth across China’s 28 provinces from 2005 to 2022, utilizing a comprehensive empirical model that integrates both provincial and annual fixed effects. Our findings reveal a significant negative impact of cybercrime on economic growth, underscoring the pressing challenge that cybercriminal activities pose to economic development. Through the application of the generalized method of moments methodology, we validate these findings, enhancing the credibility of our conclusions. An additional layer of analysis through a heterogeneity test reveals varied impacts across regions, with the eastern region most adversely affected, followed by the central and western regions. This regional disparity highlights the necessity for cybersecurity policies that are specifically tailored to the unique economic and digital landscapes of each region. Our research contributes valuable insights into the economic consequences of cybercrime in China, underscoring the critical need for targeted policy interventions to counteract these negative effects and foster economic resilience.